Dasar Pertimbangan Hakim dalam Memutus Tindak Pidana Pembunuhan yang Dilakukan oleh Anak di Bawah Umur (Analisis Putusan Nomor: 128/Pid.Sus/2013/PTY) - Imam Kholid (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2014)
This research shows that adjudicator in resolve murder case by children with caseNumber: 128/PID.Sus/2013/PTY tend to use juridical consideration that areProsecutor’s indictment, Witness’s Information, Defendant’s Information, evidence,criminal offense, and Clauses in KUHP and Children Court Regulation. In court, itfound that there is a child who didn’t accompanied by officer who was make case studywhich consist of the child’s description or condition. Besides in verification, adjudicatordidn’t call expert witness in children psychology. Meanwhile, non juridical considerationdidn’t use as consideration basis to give adjudication in case Number:128/PID.Sus/2013/PTY which based on sociology, psychology, criminology, andphilosophy of the child are didn’t used. Imprisonment provision based on sentencingpurpose review should be use double track system, if the sentencing purpose is to reprisalwithout rehabilitation and guidance isn’t yet proper because the sentencing purpose isn’tjust for reprisal, but it should brings benefit and improvement.